Efektivitas Terapi Massage Effleurage terhadap Penurunan Tingkat Stres Mahasiswa Ilmu Keolahragaan - Risang Muhammad Naufal; Bimo Alexander; Andri Arif Kustiawan; Agus Pribadi (MAN Insan Cendekia Jambi, 2026)
This study aims to analyze the effectiveness of sport massage therapy using the effleurage technique in reducing stress levels among final-year students of the Sports Science Study Program. Academic stress is highly vulnerable to final-year students completing their thesis, yet non-pharmacological relaxation interventions have not been structurally optimized. This study employed a quasi-experimental method with a pretest-posttest control group design. The participants consisted of 32 students equally divided into experimental and control groups. Data collection was conducted at Wii Sport Massage, Yogyakarta City, from May 8–25, 2026, using the Depression Anxiety Stress Scales (DASS-21) questionnaire. Analysis using the Paired Sample T-Test proved that the experimental group experienced a highly significant decrease in the average stress score from 39.43 to 25.93 (p=0.000). In contrast, the control group showed a slight increase in stress scores from 36.93 to 37.43 (p=0.041). The average N-Gain Score in the experimental group reached 70.77%. In conclusion, effleurage massage therapy is non-pharmacologically proven to be effective in reducing students' academic stress levels.